A randomised controlled trial of 'MUMentum postnatal': Internet-delivered cognitive behavioural therapy for anxiety and depression in postpartum women. (May 2019) - Loughnan, Siobhan A.; Butler, Christine; Sie, Amanda A.; Grierson, Ashlee B.; Chen, Aileen Z.; Hobbs, Megan J.; Joubert, Amy E.; Haskelberg, Hila; Mahoney, Alison; Holt, Christopher; Gemmill, Alan W.; Milgrom, Jeannette; et al.
Highlights: RCT of a brief unguided iCBT program for postpartum anxiety and depression. Large between-group superiority of iCBT over TAU for anxiety, depression, distress and bonding. Gains maintained at four-week follow-up in iCBT group. Large improvements in parenting confidence and quality of life after treatment. Participant credibility and satisfaction ratings were high with 75% program completion rate.